TelePriming sentence production in aphasia - Lee, Jiyeon; Keen, Austin D.; Farr, Ellis; Christ, Sharon (Frontiers in Human Neuroscience, 2023)
The application of videoconferencing to the assessment and treatment of aphasia has been rapidly increasing; however, there is a need to develop treatments targeting sentence production in persons with aphasia (PWA) that can be delivered through videoconferencing. Structural priming has received recent attention as a potential training method for PWA. We investigated the feasibility and efficacy of a collaborative structural priming task delivered via the internet, TelePriming, in facilitating sentence production in PWA and healthy adults.In Study 1, young adults (YA), older adults (OA), and PWA participated in a collaborative dialogue-like priming task through videoconferencing, taking turns with an interlocutor (experimenter) to describe transitive action pictures with the goal of finding matching pictures. We measured whether participants produced more passive sentences to describe their picture after hearing their interlocutor produce passive compared to active sentences (primes). In Study 2, we compared the data from the OA and PWA of Study 1 (TelePriming) to different groups of OA and PWA, who completed the same priming task in person.Results: All three groups showed robust priming effects in Study 1, producing more passive sentences to describe target pictures after hearing the experimenter produce passive versus active sentences. In Study 2, when controlling for demographic information (age, education) and aphasia severity, TelePriming resulted in larger priming effects for OA and PWA, compared to the in-person priming task. Survey results revealed that both OA and PWA experienced increased comfort and satisfaction with using technology following the task.: Interactive message-structure alignment processes remain largely intact in PWA, and the positive effects of structural priming in a collaborative communicative task are not diminished by remote delivery. The findings demonstrate the feasibility and validity of TelePriming in OA and PWA, laying experimental groundwork for future use of TelePriming in the assessment and treatment of clinical populations with limited access to face-to-face sessions.